New insights into the characterization of the electrode/electrolyte interfaces within LiMn2O4/Li4Ti5O12 cells, by X-ray photoelectron spectroscopy, scanning Auger microscopy and time-of-flight secondary ion mass spectrometry. Issue 29 (12th July 2017) - Gieu, Jean-Baptiste; Winkler, Volker; Courrèges, Cécile; El Ouatani, Loubna; Tessier, Cécile; Martinez, Hervé
Abstract : This work aims to study the electrode/electrolyte interfaces in a Li4 Ti5 O12 (LTO)/LiMn2 O4 (LMO) cell assembled with a VC-containing electrolyte and operating at 60 °C. Abstract : This work aims to study the electrode/electrolyte interfaces in a Li4 Ti5 O12 (LTO)/LiMn2 O4 (LMO) cell assembled with a VC-containing electrolyte and operating at 60 °C. LMO and LTO electrodes were mainly analyzed by X-ray Photoelectron Spectroscopy (XPS) after the first and tenth galvanostatic cycles. The XPS results indicate that both electrodes are covered by surface layers during the first charge, coming from the degradation of electrolyte species, inducing irreversible capacity losses. Although the compositions of both layers are similar, the one formed on LTO electrodes is thicker than the one formed on LMO electrodes and contains small amounts of MnF2, homogeneously spread over the surface, as revealed by the fluorine elemental mapping obtained by a complementary scanning Auger microscopy experiment. An additional measurement by time-of-flight secondary ion mass spectrometry indicates that the MnF2 is located on top of the surface layer. XPS analysis also indicates that during the first discharge, the thickness of the LTO electrode surface layer slightly decreases, due to a partial dissolution, while no changes are observed on the LMO electrode. After the tenth charge, the layers do not present any noticeable changes compared to the first charge. Interfacial layers in the LMO/LTO cell are mainly formed during the first charge, inducing an irreversible capacity loss. During the following cycles, the surface layer on LMO electrodes is stable, while it is slightly dissolved and reformed in each cycle on LTO electrodes, as suggested by the electrochemical data showing smaller and decreasing capacity losses, characteristic of the gradual passivation of these electrodes.